(3TQM SeJ GdhUhd Edi Yde GdCUhds - (3MSf GdcGaj GdHSfhj GdGbMUGQj,J (B1000 (3g` s ((3eUQ GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dHfGjI HcJGHg hHYO adeG habfi Gddg JYGdi HJCdja SeJ GdhUhd Edi Yde GdCUhd s
(3BNQgG (B:s
(3HGdVeGf aj GdeGd Ch HGdJVGef aj GdbJd GdYeO , hHGdOjI hGdcaGQI aj GdNWC, hdG TF Ydi GdecQg GdeCehQ hdjcf gPG BNQ GdcJGH s
(3Hg agQS ddehVhYGJ GdhGQO PcQgG aj GdcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3eJaQbGJs